IMPACT OF THE FOREIGN EXPERIENCE OF BOARD DIRECTORS ON THE PERFORMANCE OF PUBLICLY TRADED BRAZILIAN COMPANIES - MACHADO,VAGNER N. (2021)
ABSTRACT Purpose: We analyzed the impact of board directors with foreign experience on the accounting and market performance of companies listed on the Brazilian Stock Exchange (B3). Originality/value: We show unpublished empirical evidence about the relationship between the foreign experience of board directors and the performance of Brazilian firms. Knowing this relationship better contributes to the formulation of internal policies for the qualification of senior management, in addition to being valuable to shareholders, especially in a context of weak legal protection, as it is in Brazil. Design/methodology/approach: We collected data from 230 companies between 2010 and 2016, submitted it to unbalanced panel data regressions using the Systemic Generalized Method of Moments (GMM-Sys). Findings: The results suggest that the higher the proportion of board members with academic and professional foreign experience, the lower their accounting and market performance. This finding can be justified by institutional isomorphism, in which having an experience abroad would be a myth, a status institutionalized by the Brazilian society. In addition, foreign owners and directors face cultural barriers and would have less knowledge of the local environment, which would increase information asymmetries, impacting negatively in firms’ performance. On the other hand, an increase in the number of foreigners on the board positively influences the market value of companies, since, by having weaker local power networks and, consequently, less possibility to obtain private benefits, the investors could value companies with this characteristic.